Peranan Perempuan dalam Gereja: Eksposisi 1 Korintus 14:34 - Elim Simamora (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2019)
The position and role of women in the church need to be properly understood. This paper describes how it should be for women to take a part in the midst of God’s church. Through the case analysis of the church at Corinth will explain the purpose and purpose of Paul’s statement based on the context. Thus the church can understand what the Bible teaches about the relationship of the church and the role of women in the present.